Biological innocuousness of a device developed to select the Optimum spermatozoa to be used in the treatment of infertility - Cubilla, Marisa Angelica (2021)
The sperm selection assay (SSA) is a method based on chemotaxis to obtain spermatozoa at the optimum physiological state to successfully fertilize the egg. It consists of a device made of acrylic and an attractant solution which includes progesterone. We evaluate potential cytotoxicity interactions by means of Neutral Red uptake, the MTT and colony formation assays, according to ISO normative. Here we showed that even stressing the conditions of the assays, the SSA device alone or together with the progesterone solutions employed, showed to be innocuous for the cells. Suggesting that SSA could be incorporated into the ART procedures.